Nilai-Nilai Amanah Sebagai Strategi Fungsional Pada Rumah Makan Wong Solo Cabang Gresik - Noviandani, Martha Ineke (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aims to know and analyze the moral values of the functional strategy in the Wong Solo restaurant of Gresik branch. The aspects of the moral values consist of responsibility, globalization, truth, good working and good services. The success standard of the moral values of the functional strategy can be seen from the achievement of the employment in doing the aspects above. The research is a qualitative approach with a case study strategy. Data collection is done by using interview and observation to the object of the research. An used analysis technique is descriptive-qualitative by narrating the result of the interview and observation to the object of research. The result of this research of Restaurant Wong Solo of Gresik Branch in developing the business has been able to do some moral values well. It can be seen from the responsibility of the employments. The success by doing the moral values can also be seen by good aspect. The company gives some facilities to the employments such as: financial, and healthy. In doing operational strategy, thecompany has operational standardization in the production process. All employments perform that standardization of the rule that is stated by the company.